If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying f = 8 + -2x + -1 + x Reorder the terms: f = 8 + -1 + -2x + x Combine like terms: 8 + -1 = 7 f = 7 + -2x + x Combine like terms: -2x + x = -1x f = 7 + -1x Solving f = 7 + -1x Solving for variable 'f'. Move all terms containing f to the left, all other terms to the right. Simplifying f = 7 + -1x
| 5(x-2)=7 | | 7=-13+b | | -6.1=-1.6+x | | X/2+x/5+x=17/2 | | 20=0.10r | | 3(3k+3)-2(k-7)= | | 0.5d=18 | | (56x^3-14x^2-7x)=0 | | logy=2.2 | | 1/7x=13 | | 4^(-3/2) | | 4y-12=52 | | (5u+4)(3-u)=0 | | -12y=-156 | | -10m=150 | | (28x^3-6x^2-4x)=0 | | 17*33-28= | | -59=4+7x | | 6x-3=10x+9 | | 20=2+r | | x^2/3-5x^1/3-6=0 | | m/-22=11 | | x+3/5=3 | | m-1/6=4/7 | | 4b=-60 | | 44=4(3y-10) | | 70=0.1m^2+5m | | 10/9-x=5/12 | | 20x=2x+r | | 20x=5x | | 20pi=2pi*r | | -14+x=x+17 |